A práxis produzida pelos agentes socioeducativos no contexto da privação de liberdade - Costa, Jéssica de Morais (2021)
The National System of Socioeducative Support (SINASE) has a sanctioning character aimed at adolescents who commit an infraction and meanwhile it has as its pedagogical purpose the socio-education of adolescents. This ambivalence of roles is identified when analyzing the work developed by the socio-educational agent, especially in the units of deprivation of liberty. This research aimed to analyze the praxis produced by socio-educational agents in the context of deprivation of freedom at the Socioeducative Service Center (CASE) in Pitimbu, located in the municipality of Parnamirim. In order to do so, the sociodemographic profile and the type of training of socioeducative agents of deprivation of liberty were identified; the socioeducative practice developed by the socioeducative agents of CASE Pitimbu was characterized and the conceptions of socio-education that underlie the practice of these agents were analyzed. As an investigative method, we look for inspiration in dialectical historical materialism, seeking to analyze the real movement of the object and identifying the necessary mediations to understand it. This research has a qualitative approach and used, as data collection techniques: field research, that made it possible to observe the routine of the work developed; the application of questionnaires with the socio-educational agents who work at CASE Pitimbu, which aimed to draw a sociodemographic profile of the agents at the unit; as well as semi-structured interviews. For data analysis, meaning core was used. From the organization of the collected material (from the interviews and from the data obtained in the questionnaires), indicators were raised that revealed important meanings and meanings, considering the research objectives. After analyzing the data, it was possible to identify, based on the characterization of the agents' work, that in the daily activities of the units there is a prioritization of the logic of safety to the detriment of socio-education. This reflects not only the conception that agents formulate about the role they play in the socio-educational system, but also the way in which they are seen. Thus, the author debates the contradictions between the conceptions of socio-education and security that are revealed in the work performed by agents in the Deprivation of Liberty Unit.